2012
DOI: 10.1155/2012/798791
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Validity of a Remote Pulse Oximetry System for Pulmonary Rehabilitation: A Pilot Study

Abstract: Pulmonary rehabilitation is an effective treatment for people with chronic obstructive pulmonary disease. However, access to these services is limited especially in rural and remote areas. Telerehabilitation has the potential to deliver pulmonary rehabilitation programs to these communities. The aim of this study was threefold: to establish the technical feasibility of transmitting real-time pulse oximetry data, determine the validity of remote measurements compared to conventional face-to-face measures, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 51 publications
2
38
0
1
Order By: Relevance
“…Although we cannot assert causality in the absence of an experimental design, an increase in resting heart rate is generally considered to be an adverse outcome indicative of declining physical fitness and cardiovascular efficiency. At present, no apparent consensus has been reached on a minimal clinically important difference in resting heart rate, although changes of as few as 3 bpm have been cited (albeit with limited clinical justification 45 ). More recent research suggests that clinically important changes occur at ±5 bpm 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot assert causality in the absence of an experimental design, an increase in resting heart rate is generally considered to be an adverse outcome indicative of declining physical fitness and cardiovascular efficiency. At present, no apparent consensus has been reached on a minimal clinically important difference in resting heart rate, although changes of as few as 3 bpm have been cited (albeit with limited clinical justification 45 ). More recent research suggests that clinically important changes occur at ±5 bpm 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence supports the validity and reliability of telerehabilitation assessment for the 6MWT. These findings resonate with previous research, where telerehabilitation assessments were valid and reliable when compared with face-to-face assessments in other patient populations (Cox et al, 2013;Tang et al, 2012). For example in patients with cystic fibrosis (Cox et al, 2013), there were no significant differences in oxygen saturation, heart rate and rate of perceived exertion between telerehabilitation and face-to-face assessments for the three minute step test.…”
Section: Discussionsupporting
confidence: 89%
“…Despite these technical difficulties, patient satisfaction with telerehabilitation assessment remained high and most study participants found the system easy to use, in line with previous research (Cox et al, 2013;Tang et al, 2012). Telerehabilitation assessment may improve access; reduce travel time and cost; and reduce waiting times for specialised services such as cardiac rehabilitation programs, thereby addressing current shortcomings imposed by living in such a geographically challenging country such as Australia (Neubeck et al, 2009).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It can significantly reduce the risk of hospital admissions and improve health-related quality of life, moreover exercise training may reduce mortality in the longer term. 1,2 According to the most secondary cardiovascular prevention guidelines, regular exercise training and rehabilitation obtained the class of recommendation I, level of evidence A (indications with type I A evidence) in heart failure patients. 3,4 It can play a critical role in restoring their quality of life, and maintaining (or improving-where available) functional capacity.…”
mentioning
confidence: 99%